A systematic literature review for network intrusion detection system (IDS) - Abdulganiyu, Oluwadamilare Harazeem; Ait Tchakoucht, Taha; Saheed, Yakub Kayode (International journal of information security, 2023)
With the recent increase in internet usage, the number of important, sensitive, confidential individual and corporate data passing through internet has increasingly grown. With gaps in the security systems, attackers have attempted to intrude the network, thereby gaining access to essential and confidential information, which may cause harm to the operation of the systems, and also affect the confidentiality of the data. To counter these possible attacks, intrusion detection systems (IDSs), which is an essential branch of cybersecurity, were employed to monitor and analyze network traffic thereby detects and reports malicious activities. A large number of review papers have covered different approaches for intrusion detection in networks, most of which follow a non-systematic approach, merely made a comparison of the existing techniques without reflecting an in-depth analytical synthesis of the methodologies and performances of the approaches to give a complete understanding of the state of IDS. Nonetheless, many of these reviews investigated more about the anomaly-based IDS with more emphasis on deep-learning models, while signature, hybrid-based (signature + anomaly-based) have received minimal focus. Hence, by adhering to the principles of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), this work reviewed existing contributions on anomaly-, signature-, and hybrid-based approaches to provide a comprehensive overview of network IDS's state of the art. The articles were retrieved from seven databases (ScienceDirect, SpringerNature, IEEE, MDPI, Hindawi, PeerJ, and Taylor & Francis) which cut across various reputable journals and conference Proceedings. Among the 776 pieces of the literature identified, 71 were selected for analysis and synthesis to answer the research questions. Based on the research findings, we identified unexplored study areas and unresolved research challenges. In order to create a better IDS model, we conclude by presenting promising, high-impact future research areas.